Revision of Neoperla minor Chu with a new synonym and a new species of Neoperla Needham (Plecoptera: Perlidae) - Zeng, Liang-Liang; Huo, Qing-Bo; Du, Yu-Zhou (Zootaxa, 2024)
Neoperla yao Stark, 1987 is placed as a junior synonym of N. minor Chu, 1929. Neoperla moae sp. nov., from Zhejiang, China and misidentified previously as N. minor, is redescribed and proposed as new to science in this paper.